Evaluation and optimization on the formability of an AZ31B Mg alloy during warm incremental sheet forming assisted with oil bath heating. (June 2020) - Zhang, San; Tang, G.H.; Wang, Wenqing; Jiang, Xiangkui
Graphical abstract: Highlights: An innovative WISF assisted with oil bath heating strategy and devices was developed. An evaluation method of formability while forming the AZ31B Mg alloys was proposed. A quadratic regression model can estimates the formability in the current conditions. Abstract: This paper introduces an innovative warm incremental sheet forming approach with global heating through an oil bath setup as a heat source to form Mg alloy sheets. An attempt was made to evaluate and optimize the formability of the proposed approach using the maximum forming angle as a measure of process viability. Then, a series of experiments were conducted according to a Box-Bhenken design, including response surface methodology and an analysis of variance. Next, the results indicated the innovative approach was able to form AZ31B Mg alloy sheets with great feasibility. The most influential factor affecting the formability was the forming temperature, followed by the step depth, sheet thickness and tool diameter. The reasons for those results were also explained. Finally, the experiments validated the predictive model by evaluating an optimal combination of considered parameters for improving the formability of the AZ31B Mg alloys.